Effectiveness of cold metal transfer process for welding 7075 aluminium alloys. (21st August 2015) - Elrefaey, A.
Abstract : Cold metal transfer (CMT) welding is a promising process to improve the mechanical characteristics of the hard to weld 7075-T6 aluminium alloy owing to its unique advantages in contrast to conventional metal inert gas welding process. The welded joints, using ER5356, were identified and characterised by means of optical microscopy, scanning electron microscopy and energy dispersive spectroscopy. Mechanical properties were measured by tensile and hardness tests. Results indicate that CMT provides better joint tensile strength and ductility compared to metal inert gas welding. The softness in the heat affected zone was very low, but a big hardness gap was recognised in the welded metal compared to base metal. The joint had mechanical property coefficients of 77%, 60% and 69% for yield strength, ultimate tensile strength and elongation respectively.